Mindfulness-based relapse prevention targeting psychological craving and trait mindfulness in young Chinese women with methamphetamine dependence: a randomized controlled trial - Liu, Xuan; Zhang, Yidan; Cheng, Hongxin; Dong, Honglin; You, Yuting; Wu, Yuxi; Yang, Chunli; Jing, Lushi (Frontiers in Psychiatry, 2024)
We recruited 58 MA-dependent young adult females from a compulsory isolation drug rehabilitation center in Sichuan Province and randomly divided them into an MBRP group (n = 29) and a control group (n = 29) according to their degree of psychological craving. The MBRP group received 2 hours of MBRP training twice a week for 4 weeks, alongside routine treatment at the drug rehabilitation center. Meanwhile, the control group solely received routine treatment at the drug rehabilitation center without any additional interventions. The assessment was conducted before and immediately after the intervention, with the Compulsive Drug Use Scale (OCDUS) used to assess craving and the Five-Factor Mindfulness Scale (FFMQ) used to assess trait mindfulness. Also, a "mental feedback monitoring balance" instrument was used to assess concentration and relaxation during some training sessions. This randomized trial was conducted to evaluate the effectiveness of decreasing psychological craving and increasing trait mindfulness.At baseline, there were no significant differences in total or dimension scores for FFMQ or OCDUS between the two groups (all P > 0.05). After the intervention, the repeated measures ANOVA showed a significant time main effect on changes in observing, non-judging, and non-reacting scores (all P < 0.05), and a significant interaction effect between time and group on both FFMQ total score and OCDUS score (P < 0.01 or P < 0.05). Mental feedback monitoring indicated significant improvement in concentration and relaxation after breath meditation exercises (P < 0.05 or P < 0.001). Additionally, the MBRP group showed improved relaxation during the body scan exercise (P < 0.01).MBRP training can improve the trait mindfulness of MA addicts and reduce psychological cravings effectively.